2021
DOI: 10.14740/jocmr4518
|View full text |Cite|
|
Sign up to set email alerts
|

Review of COVID-19 Variants and COVID-19 Vaccine Efficacy: What the Clinician Should Know?

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a beta coronavirus that belongs to the Coronaviridae family. SARS-CoV-2 is an enveloped spherical-shaped virus. The ribonucleic acid (RNA) is oriented in a 5'-3'direction which makes it a positive sense RNA virus, and the RNA can be read directly as a messenger RNA. The nonstructural protein 14 (nsp14) has proofreading activity which allows the rate of mutations to stay low. A change in the genetic sequence is called a mutation. Genomes that diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 21 publications
0
144
1
4
Order By: Relevance
“…In the era of COVID-19 variants and the new mutations of the virus, there is always a potential of atypical presentations of the COVID-19 infection [16,17]. The hesitancy around taking the widely available COVID-19 vaccinations has also contributed to the recurrent and ongoing waves of the pandemic [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of COVID-19 variants and the new mutations of the virus, there is always a potential of atypical presentations of the COVID-19 infection [16,17]. The hesitancy around taking the widely available COVID-19 vaccinations has also contributed to the recurrent and ongoing waves of the pandemic [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Experience with the SARS-CoV-2 vaccination programmes showed that protective immunity gained by natural infection with SARS-CoV-2 is poor compared to the much higher levels of virus-neutralizing antibodies and T cells induced by the vaccines [101,102]. An emerging problem is the development of new variants of SARS-CoV-2 with the ability to escape natural and vaccine-induced immunity [103,104]. This fact prompts the need for updated vaccines [105], and confirms that a global vaccination program with high efficacy vaccines is one of the most important challenges of the next years.…”
Section: Reinfection With Sars-cov-2-when Does It Occur and How Can It Be Verified?mentioning
confidence: 99%
“…Thus, current vaccines must be continuously refined to stay protective. Although the vaccines are an effective critical tool, none of them are a 100% effective in the prevention of COVID-19 illness [103]. A small percentage of the fully immunized population will show vaccine breakthrough cases.…”
Section: What Is the Difference Between Naturally Acquired Immunity And Vaccine-mediated Immunity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer and less consistent data have been obtained with the P.1 (gamma) variant. The P.1 (gamma) variant was identified for the first time in the city of Manaus, North Brazil, in December 2020 and further in passengers from Brazil tested at an airport nearby Tokyo [ 7 ]. Variant spike protein substitutions are L18F, T20N, P26S, D138Y, R190S, K417T, E484K, N501Y, D614G, H655Y, and T1027I [ 8 ].…”
Section: Introductionmentioning
confidence: 99%